APLIKASI CITRA ALOS AVNIR-2 UNTUK PEMETAAN DISTRIBUSI MUATAN PADATAN TERSUSPENSI (TOTAL SUSPENDED SOLIDS) DI MUARA SUNGAI OPAK YOGYAKARTA - , MARINDAH YULIA ISWARI, Prof. Dr. Hartono DEA., DESS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
ALOS AVNIR-2 is one of remote sensing images that can be used to monitor water quality. One of water quality that can be extracted from remote sensing is total suspended solids (TSS). This research aims to know TSS estimation use algorithms from previous researches, to test comparation between TSS from remote sensing estimation and in situ data, and to map TSS distribution in Opak Estuary. Three algorithms which used are Hendrawan and Asai (2008), Bhatti et.al (2011) and Alashloo et.al (2013). T-test that used to compare between estimation data and in situ data result that three algorithms can not be used because it does not match with in situ data. A new model to estimate TSS are made from regression between NDSSI and in situ data. NDSSI is a suspended sediment index that resulted from remote sensing. NDSSI is an index which explained that +1 is a clear water and -1 is a turbid water. Accuracy of this model has standard error estimation 18.9%. TSS distribution in Opak Estuary shows that TSS concentration between 3-100 mg/l. TSS high concentration can be found in area that has sediment accumulation. This area usually can be seen at dry season but this area get wet and covered by flood at rainy season. TSS distribution was influenced by many factors such as land use, geology, sediment material and water waves. Keywords : ALOS AVNIR-2, total suspended solids, t-test, regression, NDSSI